2020
DOI: 10.3389/fnagi.2020.00243
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Acoustic-Based Interventions to Improve Motor Symptoms in Parkinson’s Disease

Abstract: Parkinson's disease (PD) is characterized by motor and cognitive deficits that negatively impact on activities of daily living. While dopaminergic medications are used to attenuate motor symptoms, adjuvant therapies such as acoustic-based non-pharmacological interventions are used as a complement to standard drug treatments. At present, preliminary studies of acoustic-based interventions such as rhythmic-auditory stimulation (RAS) and vibroacoustic therapy (VAT) suggest two competing hypotheses: (1) RAS may re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Dopaminergic drugs are used to lessen motor symptoms, while adjuvant therapies, such as acoustic-based non-pharmacological interventions, are utilized as a supplement to 10.3389/fnhum.2023.1100431 conventional drug treatments. Numerous studies have shown that rhythmic auditory stimulation (RAS) can help Parkinson's disease sufferers walk more naturally (Lee et al, 2012;Benoit et al, 2014;Leuk et al, 2020). For instance, walking to an audio metronome can reduce timing variability, increase walking speed, and lengthen strides (Benoit et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Dopaminergic drugs are used to lessen motor symptoms, while adjuvant therapies, such as acoustic-based non-pharmacological interventions, are utilized as a supplement to 10.3389/fnhum.2023.1100431 conventional drug treatments. Numerous studies have shown that rhythmic auditory stimulation (RAS) can help Parkinson's disease sufferers walk more naturally (Lee et al, 2012;Benoit et al, 2014;Leuk et al, 2020). For instance, walking to an audio metronome can reduce timing variability, increase walking speed, and lengthen strides (Benoit et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Two main hypotheses have been formulated to explain how RAS may compensate the timing deficit in PD, the compensation and restoration hypotheses (for review, see [ 50 ]). The compensation theory proposes that areas other than the basal ganglia are activated to substitute the basal ganglia in rhythm perception and are linked to the internal processing of timing.…”
Section: Discussionmentioning
confidence: 99%
“…A digital therapeutic platform (MedRhythms Inc.) has been designed to improve walking outcomes by digitizing a well-established, evidence-based intervention known as Rhythmic Auditory Stimulation (RAS). RAS is an approached used in rehabilitation in which external auditory cues (e.g., beat of a metronome) are applied to facilitate entrainment or the ability to synchronize movements (i.e., walking) to a beat [ 9 ]. Several studies reveal the beneficial effects of RAS in improving spatiotemporal parameters of gait in PD [ 10 ], but translation of this approach into digital therapeutics is just beginning.…”
Section: Digital Therapeutics To Improve Walking Outcomesmentioning
confidence: 99%